Respostas
respondido por:
2
Podemos usar o método da substituição.
u = -x
du = - dx
dx = - du
Então a integral fica
integral de (e^u . -du) =
= - integral de (e^u du) =
= - e^u
mas
u = -x
Então,
integral de (e^u . (-du)) = - e^-x (de 0 a 1)
Integral = ( - e^-1 )-( - e^-0)
integral = ( - e^-1 )-( -1)
integral = - (e^-1)+1
integral = 1 - e^-1
u = -x
du = - dx
dx = - du
Então a integral fica
integral de (e^u . -du) =
= - integral de (e^u du) =
= - e^u
mas
u = -x
Então,
integral de (e^u . (-du)) = - e^-x (de 0 a 1)
Integral = ( - e^-1 )-( - e^-0)
integral = ( - e^-1 )-( -1)
integral = - (e^-1)+1
integral = 1 - e^-1
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás